Optimizing Fixed Asset Management through Information System at BPJS Ketenagakerjaan Belawan Medan Branch - Zebua, Heppi Ratnawati; Khairunnisa, Khairunnisa; Sihombing, Monang Juanda Tua (Jurnal Komputer Indonesia (Ju-Komi), 2022)
This research aims to enhance the efficiency of fixed asset management at BPJS Ketenagakerjaan Belawan Medan Branch through the implementation of a Fixed Asset Information System. The primary focus involves system requirement analysis, database design, and application development to optimize the maintenance and management of the organization's fixed assets. Data is obtained through interviews with relevant staff, observation of current processes, and analysis of internal documents. The research methodology encompasses the development of a system that can effectively monitor, record, and report information related to fixed assets. It is anticipated that the implementation of this system will improve the accuracy of asset tracking, reduce the potential for data loss, and provide a better understanding of the condition and utilization of fixed assets, thereby supporting more informed decision-making at the BPJS Ketenagakerjaan Belawan Medan Branch level.